Robust water splitting on staggered gap heterojunctions based on WO3∖WS2–MoS2 nanostructures. (December 2020) - Mojaddami, Majdoddin; Simchi, Abdolreza
Abstract: The high charge carrier recombination rate and weak oxygen evolution kinetics have impeded the efficiency of WO3 photoelectrodes for water splitting. We present a novel type II heterojunction semiconductor based on mixed WS2 and MoS2 nanosheets on WO3 nanoflakes hydrothermally grown on highly porous W skeletons. The chemically exfoliated transition metal dichalcogenide (TMD) sheets with submicrometric lateral sizes were deposited on the surface of WO3 nanoflakes by the electrophoretic technique to fabricate a staggered gap heterojunction. The photoanode exhibited an impressive current density of 14.9 mA cm −2 at 1.23 VRHE which comprised ∼1.7 mA cm −2 photocurrent under 100 mW cm −2 simulated sunlight. Co-deposition of MoS2 and WS2 sheets on WO3 nanoflakes improved the current density of porous W∖WO3 electrodes by about 340%, while only about 36% improvement is achieved by deposition of single TMD (WO3 ∖MoS2 or WO3 ∖WS2 ) demonstrating the synergetic effects of TMDs. The high stability of the photoanode in highly acidic media is shown. The synergetic effects of TMDs on active sites, charge transfer resistance, and charge transport properties are elaborated by electrochemical impedance spectroscopy and Mott-Schottky analyses. The composite electrode has a great potential to be used for diverse electrochemical applications including water splitting. Graphical abstract: Image 1 Highlights: A novel staggered gap heterojunction of WO3 /WS2 –MoS2 nanostructures was prepared. The synergetic effect of TMD nanosheets on OER activity of WO3 was shown. A remarkable current density of 14.9 mA cm −2 at 1.23 VRHE was achieved. EIS showed superior electron transport in the composite photoelectrode.